(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Spinal tuberculosis is secondary tuberculosis; the disease progresses through several stages with complicated development. Spinal tuberculosis needs to be detected early and treated promptly. Accurate diagnosis of spinal tuberculosis requires a combination of clinical, laboratory, and imaging studies. In contributing to clarifying spinal tuberculosis’s diagnostic features, we analyzed clinical features, computed tomography, and magnetic resonance imaging on 135 patients with thoracic, lumbar spine tuberculosis with neurological complications treated at the National Lung Hospital. Goals: 1, Assess clinical characteristics of patients with tuberculosis of thoracic and lumbar spine with neurological complications; 2, Assess the characteristics of computed tomography and magnetic resonance imaging in patients with tuberculosis of the thoracic and lumbar spine with neurological complications. Research method: Cross-sectional description. Results: 61.5% of patients had chronic anemia, average motor score: 86,3±13,4 points; average pain score according to VAS: 6,7±0,62 points; average thoracic kyphosis angle: 28,20 ± 9,30; average lumbar kyphosis angle: 1,00 ± 18,90. On computed tomography and magnetic resonance imaging: 85.1% of patients had abscesses; 96.3% had moderate to severe vertebral destruction. The most distinctive features of spinal tuberculosis include: Moderate to severe vertebral destruction; Mild to moderate disc degeneration; paraspinal abscess with well-defined margin; vertebral intraosseous abscess with rim enhancement; heterogeneous and focal enhancement of the vertebral body... Conclusion: Diagnosis of spinal Tuberculosis based on clinical; computed tomography; and magnetic resonance imaging gives high accuracy results with many specific signs of spinal tuberculosis.